Hepatitis due to Coxsackie A virus in an adult: a case report - Likith Surendra; Varun Sharma; Milan Sivakumar; Tara Lanzendorf; Thomas C. Varkey; Kaivan Salehpour (Egyptian Liver Journal)
Abstract Background Coxsackie A16, an Enterovirus and cause of hand-foot-and-mouth disease in children, is characterized by fever and erythematous papular eruptions. Coxsackie virus-induced hepatitis has also been established in children; however, it has been rarely reported in the adult population. We present a unique case of an adult male with acute hepatitis from Coxsackie A exposure. Furthermore, this case highlights the value of obtaining a detailed history, as practitioners may overlook minute details that are key to developing an accurate care plan. Case presentation The patient is a 35-year-old male who presented with acute epigastric and right upper quadrant pain. His past medical history was significant for asthma, chronic back pain taking tramadol, cholecystitis status post cholecystectomy, and an ongoing workup for autoimmune hepatitis. He was found to be febrile to 100.9 °F, with leukocytosis of 12.6 × 109 WBC/L, elevated liver function tests (LFTs) including aspartate aminotransferase (AST) of 386 U/L and alanine transaminase (ALT) of 260 U/L, and elevated total bilirubin of 2.2 mg/dL. The day after presentation, AST increased to 694 U/L, and ALT increased to 594 U/L. Physical examination, abdominal imaging, and laboratory testing for classic viral causes of hepatitis were unremarkable. The internal medicine team initially assessed the patient to have acute hepatitis that was autoimmune or drug-induced in nature. However, after more careful history taking, the patient was found to have exposure to hand-foot-and-mouth disease through his young son. The team subsequently ordered an expanded viral panel, which was positive for Enterovirus. Based on the patient’s exposure history, this was determined to be Coxsackie A. The patient was subsequently treated successfully with supportive care. Conclusions Coxsackie virus causing hepatitis in adults has been rarely reported. This unique case demonstrates Coxsackie A-induced hepatitis in an adult due to exposure from a sick contact. Given the patient’s history of potential autoimmune and tramadol-induced hepatocyte damage, our case suggests that Coxsackie A may be more virulent in a patient with underlying liver vulnerability. Our case also highlights the importance of obtaining a thorough history to ensure appropriate treatment and prevent delays in management.